Polaron Model of Traps and their Activation Energies in KBr Crystals - Рћ.В Stanovyi; S.В Рљutovyy; A.В Gumenyuk; Р†.В Dmitruk (Журнал нано- та електронної фізики)
The activation energy spectrum of traps in KBr crystals has been studied by the thermoluminescence (TL) methods in the temperature range of 80-450 Рљ. The energies of thermal activation of traps in KBr were found to form an oscillator-like series , with the vibrational quantum energy 0.078В eV (629В cmВ вЂ“В 1). Using the generalization of the data on other investigated alkali halides crystals the early-proposed model of the TL in alkali halides based upon two-stage recombination of the H-centers was confirmed. The energy of the quantum in oscillator regularity corresponds to the local vibration mode of the halide molecule .